Arthropods Diversity on Soybean Fields with Integrated Pest Management and Conventional Systems in Gandusari District, Blitar Regency - Mahendra, Niko; Rahardjo, Bambang Tri; Widjayanti, Tita (University of Brawijaya, 2023)
Various negative impacts of pesticides must be avoided by applying management principles that have as little negative impact on the environment as possible using an integrated pest management (IPM) approach. This study aimed to examine the diversity of arthropods and the feasibility of farming in IPM and conventional fields on soybeans. Arthropod sampling was carried out in September–December 2021 using a yellow pan trap, yellow sticky trap, and visual methods. The arthropod population found was analyzed using the T-test, and the level of arthropod diversity was calculated based on the diversity index (H'), species richness index (R), evenness index (E), and dominance index (C). The feasibility of farming on both fields was calculated using the R/C ratio and BEP prices. The results showed that the number of arthropods in IPM and conventional fields was significantly different. In both fields, the diversity index value was in the medium category, the species richness index value and the evenness index value were in the high category, and there was no dominance in both fields. Even though it belonged to the same category, the index value of arthropod diversity in the IPM field was higher than in the conventional field. In IPM and conventional fields, the R/C ratio values were 1.01 and 1.06, respectively, while the BEP value in IPM and conventional fields was IDR 10,601.44 and IDR 10,075.14.